Semantics of Asynchronous JavaScript - Loring, Matthew C.; Marron, Mark; Leijen, Daan (DLS '17 - Proceedings of 13th ACM SIGPLAN International Symposium on Dynamic Languages, 2017)
The Node.js runtime has become a major platform for developers building cloud, mobile, or IoT applications using JavaScript. Since the JavaScript language is single threaded, Node.js programs must make use of asynchronous callbacks and event loops managed by the runtime to ensure applications remain responsive. While conceptually simple, this programming model contains numerous subtleties and behaviors that are defined implicitly by the current Node.js implementation. This paper presents the first comprehensive formalization of the Node.js asynchronous execution model and defines a high-level notion of async-contexts to formalize fundamental relationships between asynchronous events in an application. These formalizations provide a foundation for the construction of static or dynamic program analysis tools, support the exploration of alternative Node.js event loop implementations, and provide a high-level conceptual framework for reasoning about relationships between the execution of asynchronous callbacks in a Node.js application.